“Being safe means you can feel uncomfortable”: a case study of female students’ participation in a higher education, online improvisation course - MacGlone, Una M. (Frontiers in Education, 2023)
In higher music education (HME), improvisation is a developing area of practice and research interest across different genres and courses. However, professional jazz and improvised performance contexts, which have strong connections with HME, have been conceptualised as ‘masculine’ spaces. As an important pathway towards the music profession, HME may provide a place where hegemonic discourses can be challenged. The pandemic necessitated HME’s shift online and thus provided new environments for learning group improvisation. A qualitative study with four female students was undertaken to investigate their experiences and views about an online free improvisation course. Research questions considered (1) how female students understood their learning space in an online free improvisation module and (2) what possibilities were available for creative and musical actions. A focus group and individual interviews were held after the course. Two themes were identified: the deep end and new materials, new space. Students used a common metaphor of being ‘in the deep end’. However, they framed this positively, either as feeling safe to experiment musically or in overcoming feelings of discomfort, perceiving an increase in self-efficacy. Findings also demonstrated that students were able to exercise agency and customize their online space by using filters, changing backgrounds, and choosing when to turn their cameras on and off. Appreciating female students’ perspectives and trajectories of participation can inform teachers’ priorities for creating an optimal and inclusive space for learning improvisation.